2006
DOI: 10.1177/0363546506295026
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts Review: Revision Anterior Cruciate Ligament Reconstruction

Abstract: Failed anterior cruciate ligament (ACL) reconstruction presents a difficult clinical challenge. Successful revision ACL reconstruction depends on identifying the causes of failure and correcting technical or diagnostic errors. Failed ACL reconstruction may be either traumatic or atraumatic. Atraumatic failures may be attributable to technical errors, diagnostic errors, or failure of graft incorporation. Published outcomes of revision ACL reconstruction have been worse than for primary ACL reconstruction. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
215
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(225 citation statements)
references
References 75 publications
3
215
1
6
Order By: Relevance
“…Patient education is crucial to carryover the home exercises designed to address knee extension ROM, with the frequency of physical therapy sessions established to maximize early return of full knee extension ROM. It is important to recognize that even a loss of less than 5 degrees of knee extension ROM can lead to long-term patellofemoral pain issues, quadriceps strength deficits and a bent-knee gait abnormality [13,14]. Sample exercises and interventions for improving knee extension ROM are presented in Table 1.…”
Section: Early Post-operative Complicationsmentioning
confidence: 99%
“…Patient education is crucial to carryover the home exercises designed to address knee extension ROM, with the frequency of physical therapy sessions established to maximize early return of full knee extension ROM. It is important to recognize that even a loss of less than 5 degrees of knee extension ROM can lead to long-term patellofemoral pain issues, quadriceps strength deficits and a bent-knee gait abnormality [13,14]. Sample exercises and interventions for improving knee extension ROM are presented in Table 1.…”
Section: Early Post-operative Complicationsmentioning
confidence: 99%
“…1) and detect potential anomalies like elongation, recurrent tears, increased postoperative laxities. These may occur in graft malpositioning [89,90] or graft failures [91]. Numerous studies reported knee laxity measurements at a specific time point after ACL reconstruction.…”
Section: Knee Laxity After Anterior Cruciate Ligament Reconstructionmentioning
confidence: 99%
“…A vertical femoral tunnel has been cited as 1 of the most common causes for failure of ACL reconstruction. 12,21,22 Background: There is controversy regarding the necessity of reconstructing both the posterolateral and anteromedial bundles of the anterior cruciate ligament. …”
mentioning
confidence: 99%